Electrochemical sensing of nitrite using a copper–titanium oxide composite derived from a hexanuclear complex. Issue 33 (16th March 2016) - Ehsan, Muhammad Ali; Naeem, Rabia; McKee, Vickie; Saeed, Abbas Hakeem; Pandikumar, Alagarsamy; Huang, Nay Ming; Mazhar, Muhammad
Abstract : An electrochemical nitrite ions sensor electrode, CuO–2TiO2, has been developed using single molecular precursor [Cu2 Ti4 (O)2 (OH)4 (TF)8 (THF)6 ]·THF in aerosol assisted chemical vapour deposition technique. Abstract : A hexanuclear copper–titanium complex [Cu2 Ti4 (O)2 (OH)4 (TFA)8 (THF)6 ]·THF (1 ) (where TFA = trifluoroacetato, THF = tetrahydrofuran) has been identified for the treatment of copper(ii ) acetate with titanium(iv ) isopropoxide and trifluoroacetatic acid in THF. The physicochemical properties of complex (1 ) have been inspected by melting point analysis, microanalysis, attenuated total reflectance Fourier transform infrared spectroscopy, thermogravimetry and single crystal X-ray analysis. The "single source" potential of complex (1 ) has been explored by a solution based aerosol assisted chemical vapor deposition method to fabricate CuO–2TiO2 composite oxide thin films on a fluorinated tin oxide (FTO) conducting glass substrate at 550 °C in ambient air. Thin film characterization such as X-ray powder diffraction, Raman spectroscopy and X-ray photoelectron spectroscopy, energy dispersive X-ray and scanning electron microscopic analyses confirm the evolution of crystalline CuO: a 2TiO2 composite with spherical morphology, with clear grain boundaries and in high purity. Further, the well-characterized film electrode was investigated for electrochemical detection of nitrite ions (NO2 − ). The fabricated CuO–2TiO2 electrode showed a peak at +1.0 V due to the oxidation of NO2 − ions. The limit of detection (LoD) was found to be 0.0166 μM, with the linear range of 10 to 200 μM. Moreover, this present sensor is more selective towards NO2 − ions and it did not show any response to other interfering species. This CuO–2TiO2 electrode is a potential candidate for the selective and sensitive detection of toxic NO2 − ions towards monitoring the NO2 − ion levels in natural water sources for environmental remediation applications.